ASSESSMENT OF RECOVERY BALANCING STROKE PLATFORMS THROUGH POST BAROPODOMETRY - Danelciuc Francisc Tadeus; Danelciuc Elena Mihaela; Betiuc Mihail (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Coordination abilities manifes in different forms, one being the ability to balance, having a major role in the static, walking, the daily activities of persons after stroke. The study aims to highlight the benefits that can offer an appropriate and judicious use equipment to recover people after stroke, both to assess the balance with electronic baropodometry